RESPON COUNCIL OF PALM OIL PRODUCING COUNTRIES (CPOPC) DALAM MENGHADAPI KEBIJAKAN RENEWABLE ENERGY DIRECTIVE II (RED II) UNI EROPA - Benyamin, Siti Rayya Putri; Jamaan, Ahmad (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2024)
The Council of Palm Oil Producing Countries (CPOPC) is an international organization established by palm oil-producing countries, namely Indonesia and Malaysia. CPOPC was formed to coordinate strategic measures in maintaining the positive image of palm oil products and addressing challenges in international trade. The European Union's actions, deemed protectionist—particularly through the RED II policy that excludes palm oil from the renewable energy sector—are the focus of this study. This paper aims to examine how CPOPC responds to such policies. The research employs a qualitative method, with data collection techniques including literature studies from books, journals, articles, and websites. The study uses the Neoliberal Institutionalism perspective and the theory of economic diplomacy. The findings conclude that CPOPC has responded to the RED II policy using economic diplomacy in the form of persuasive measures, such as diplomatic negotiations and technical discussions. However, these efforts have not succeeded in changing the European Union's decision. The RED II policy remains in effect without significant modifications in response to CPOPC's requests or objections. This indicates that CPOPC lacks substantial bargaining power or coercive influence over the European Union. Keywords: Crude Palm Oil, Protectionism, European Union, Economic Diplomacy